2019
DOI: 10.1111/aec.12749
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers of species composition and functional diversity of dung beetles along the Atlantic Forest–Pampa transition zone

Abstract: Human activities are causing a rapid loss of biodiversity, which impairs ecosystem functions and services. Therefore, understanding which processes shape how biodiversity is distributed along spatial and environmental gradients is a first step to guide conservation and management efforts. We aimed to determine the relative explanatory importance of biogeographic, environmental, landscape and spatial variables on assemblage dissimilarities and functional diversity of dung beetles along the Atlantic Forest-Pampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 110 publications
(142 reference statements)
0
4
1
Order By: Relevance
“…In this context, the objective of this study was to compare the taxonomic and functional response of dung beetles to livestock under two different environmental management regimes in the Dry Chaco: open pastures and silvopastoral systems with native tree canopy. Whereas studies performed in humid forests showed a marked decrease in taxonomic and functional diversity of dung beetles in livestock areas (Audino et al, 2014;Gómez-Cifuentes et al, 2017;da Silva & Cassenote, 2019;Guerra Alonso et al, 2019), based on the few studies performed in dry forests, we did not expect a marked influence in the Dry Chaco. Moreover, we expected that cattle systems preserving native canopy will support higher taxonomic and functional richness and greater similarity in dung beetles community composition to native forest than open pastures.…”
Section: Introductioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In this context, the objective of this study was to compare the taxonomic and functional response of dung beetles to livestock under two different environmental management regimes in the Dry Chaco: open pastures and silvopastoral systems with native tree canopy. Whereas studies performed in humid forests showed a marked decrease in taxonomic and functional diversity of dung beetles in livestock areas (Audino et al, 2014;Gómez-Cifuentes et al, 2017;da Silva & Cassenote, 2019;Guerra Alonso et al, 2019), based on the few studies performed in dry forests, we did not expect a marked influence in the Dry Chaco. Moreover, we expected that cattle systems preserving native canopy will support higher taxonomic and functional richness and greater similarity in dung beetles community composition to native forest than open pastures.…”
Section: Introductioncontrasting
confidence: 71%
“…In contrast to taxonomic diversity, the response of dung beetle functional diversity to disturbance has been less explored. However, recent studies show similar patterns of functional diversity reduction following forest replacement by cattle pastures (Gómez-Cifuentes et al, 2017;da da Silva & Cassenote, 2019).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Seasonality and the total amount of precipitation were the major differences among regions in this study. Consistent with this pattern, Nichols et al 55 , proposed that the functional response of dung beetles to anthropogenic disturbance depends on the regional context whereas da Silva and Cassenote 53 proposed that climatic seasonality is the main determinant of functional dung beetles response. Environmental dissimilarity between native habitats and land uses has already been identified as one of the main predictors of changes in biological assemblages at both local and regional scales 20 , 58 .…”
Section: Discussionmentioning
confidence: 92%
“…While previous studies explored either local or regional functional responses of dung beetles to environmental gradients or human disturbances 29 , 30 , 53 55 ; this is the first study that simultaneously explore both components through the comparison of similar land uses among different regions. Consistent with previous studies, the replacement of native forest by open pastures strongly reduced functional diversity in humid forest and showed low impact on dry forests 27 , 29 , 56 .…”
Section: Discussionmentioning
confidence: 99%